SETTLEMENT OF DEFAULT CASES IN THE SALE-PURCHASE AGREEMENT OF AGRICULTURAL PRODUCTION FACILITIES THROUGH NON-LITIGATION METHODS (STUDY AT PT. PETROSIDA GRESIK) - Virginia, Zalsha Bella; Sri Maharani M.T.V.M., Sri (fakultas hukum universitas PGRI Semarang, 2025)
Default cases related to the sale and purchase of agricultural production facilities continue to arise often during the implementation of the agreement between PT. Petrosida Gresik and some of its purchasers or distributors. Hence, the purpose of this research is to analyze the reasons, attempts to minimize, and nonlitigation settlement of cases in the hopes that there will be no more or at least a reduction in the number of cases. This study employs an empirisal legal research method with descriptive research and qualitative data analysis.According to the research results, buyers or distributors experience natural disasters, unhealthy competition, are exposed to fraud, and are unable to manage their finances, thus committing defaults. Efforts to minimize them have also been made. Then, the non-litigation case settlement process partly uses the newest efforts by PT. Petrosida Gresik with the results of successful and unsuccessful settlements, which are continued through litigation.